2000
DOI: 10.1142/s0192415x00000210
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects ofArctium Lappaon Carbon Tetrachloride- and Acetaminophen-Induced Liver Damage

Abstract: The root of Arctium lappa Linne (A. lappa) (Compositae), a perennial herb, has been cultivated for a long time as a popular vegetable. In order to investigate the hepatoprotective effects of A. lappa, male ICR mice were injected with carbon tetrachloride (CCl4, 32 microl/kg, i.p.) or acetaminophen (600 mg/kg, i.p.). A. lappa suppressed the SGOT and SGPT elevations induced by CCl4 or acetaminophen in a dose-dependent manner and alleviated the severity of liver damage based on histopathological observations. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 25 publications
3
43
0
2
Order By: Relevance
“…The high degree of fatty deposition found in the liver of one animal of group A and one in group B, was not considered to be a consequence of the treatment, since it occurred in few individuals only. The results supported the concept that hepatoprotective effects could be attributed to A. lappa in relation to liver injuries induced by chronic ethanol consumption, or chronic ethanol consumption potentiated by carbon tetrachloride (Lin et al, 2002), tetrachloride and acetaminophen (Lin et al, 2000). However, this study in animals suggested that caution should be taken in using A. lappa to treat human patients with kidney stones and gout, since the plasmatic levels of uric acid were somewhat increased in the treated groups.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The high degree of fatty deposition found in the liver of one animal of group A and one in group B, was not considered to be a consequence of the treatment, since it occurred in few individuals only. The results supported the concept that hepatoprotective effects could be attributed to A. lappa in relation to liver injuries induced by chronic ethanol consumption, or chronic ethanol consumption potentiated by carbon tetrachloride (Lin et al, 2002), tetrachloride and acetaminophen (Lin et al, 2000). However, this study in animals suggested that caution should be taken in using A. lappa to treat human patients with kidney stones and gout, since the plasmatic levels of uric acid were somewhat increased in the treated groups.…”
Section: Discussionsupporting
confidence: 76%
“…This plant has long been cultivated as a vegetable for dietary use and is also used as a folk medicine, as a diuretic, antipyretic tea (Chen et al, 2004) as well as for hypertension, gout, hepatitis and other inflammatory disorders (Lin et al, 2002). Several studies have reported that the burdock possesses various pharmaceutical activities including an antibacterial activity (Pereira et al, 2005;Chen et al, 2004), antifungical activity (Pereira et al, 2005), antiplatelet-aggregating effect (Pereira et al, 2005;Lin et al, 2002), an antioxidant (Chen et al, 2004;Pereira et al, 2005;Leonard, et al, 2006), hepatoprotective efficacy (Lin et al, 2000;Lin et al, 2002) and anti-inflammatory activity (Lin et al, 1996;Chen et al, 2004). Pereira et al (2005) have demonstrated that A. Lappa exhibits antimicrobial activity against oral microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…For hepatoprotective effect, burdock was shown to suppress the CCl 4 or acetaminophen-intoxicated mice as well as the ethanol plus CCl 4 -induced rat liver damage. The underlying hepatoprotective ability of burdock could be related to the decrease of oxidative stress on hepatocytes by increasing glutathione (GSH), cytochrome P-450 content and NADPH-cytochrome c reductase activity and by decreasing malondialdehyde (MDA) content, hence alleviating the severity of liver damage based on histopathological observations (Lin et al, 2000;Lin et al, 2002). In summary, the anti-inflammatory action of burdock is attributed to its high free radical scavenging capacities and antioxidant activity.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Burdock (Arctium lappa L.), a biennial plant belonging to the Compositae family, has been cultivated in Eastern Asian countries, particularly in Taiwan, China and Japan for use in cooking and in folk medicine as a diuretic, antipyretic and blood purifying agent (8-10). Pharmacologically, burdock has been identified to possess hepatoprotective (11,12), desmutagenic (13), antibacterial (14,15), gastroprotective (16,17), anti-hypoglycemic (18,19), anti-hypolipidemic (20), anti-inflammatory (21), antifatigue (22), antioxidant (10,21,23), body weight management (24) and aphrodisiac (25) activities. Therefore, burdock-containing health drinks and foods are widely consumed in Taiwan.…”
Section: Introductionmentioning
confidence: 99%